ROLE OF NON PERFORMING ASSETS – A MSMEs PERSPECTIVE - Dr.J.Venkatesh, Ms.R.Lavanya Kumari (International Journal of Research Science and Management, 2015)
This article is to provide an insight into the concept of Non-Performing Asset(NPA), a standard criterion for Micro Small Medium Enterprises sector.An asset becomes non performing when it ceases to generate income for the Bank. Non-performing assets are one of the biggest challenges facing the global banking system, and particularly Indian banks. The extent of the challenge for nationalized banks is that non-action is no longer an option. But on the same time SME units are prone to various business risks due to which they fall sick or sometimes closed due to heavy losses or many of them becomes NPA in the accounts of the banks. This issue is likely to get worse due to the overall economic slowdown impacting most customer segments across banks’ portfolio like MSMEs (Micro, Small and Medium Enterprises), large corporates, and agriculture.